Transplacentally transmitted organophosphorous compound poisoning in a newborn : Acase report and narrative review of literature (Bangladesh Critical Care Journal, 2020)
Organophosphorous compound (OPC) poisoning in the newborn is a medical emergency but completely treatable condition. Early recognition and treatment is of paramount importance in preventing fatality. A newbornmale of severe perinatal asphyxia was admitted in our neonatal intensive care unit (NICU) with a history of maternal OPC poisoning 31 hours before delivery. We treated the case on urgent basis, had stormy neonatal course and finally baby went home safely. OPC poisoning in newborn is a rare occurrence in the tropics. We report a rare case of transplacentally transmission of OPC poisoning innewborn and it is going to be 3rd and latest such reported case across the world upon literature search.Bangladesh Crit Care J September 2020; 8(2): 120-123